Observed Antarctic sea ice expansion reproduced in a climate model after correcting biases in sea ice drift velocity - Shantong Sun (Nature Portfolio, 2021)
Climate models typically fail to capture the observed Antarctic sea ice expansion during recent decades. Here, the authors show that the observed expansion is reproduced in a climate model after removing biases in the sea ice drift velocity.